2003
DOI: 10.1021/la027053+
|View full text |Cite
|
Sign up to set email alerts
|

Redox Controlled Partition and Spatial Distribution of Solvent and Salt in Electroactive Polyvinylferrocene Films

Abstract: In situ neutron reflectivity measurements have been made on spin cast polyvinylferrocene (PVF) films maintained under electrochemical potential control. The data show that the interiors of both oxidized and reduced films are close to homogeneous. The results show that neutron reflectivity measurements, including isotopic substitution, can provide novel insights into film composition and structure at the electrode/ polymer/solution interface. Isotopic substitution of the solvent has allowed the contributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 22 publications
1
57
1
Order By: Relevance
“…Such competitive anion ingress and cation egress processes for charge compensation are well known for both conductive polymer and redox polymer thin films. [54][55][56][57] Taken together, it is reasonable to assume that the first and third terms of Equation 2 are comparable for SAM2 and SAM2b. Therefore, by comparing the SPR angle changes for each, we have a means to quantify the contribution film reorganization alone, and to estimate the SAM thickness change (Δd) upon oxidation of the Fc label.…”
Section: Discussionmentioning
confidence: 99%
“…Such competitive anion ingress and cation egress processes for charge compensation are well known for both conductive polymer and redox polymer thin films. [54][55][56][57] Taken together, it is reasonable to assume that the first and third terms of Equation 2 are comparable for SAM2 and SAM2b. Therefore, by comparing the SPR angle changes for each, we have a means to quantify the contribution film reorganization alone, and to estimate the SAM thickness change (Δd) upon oxidation of the Fc label.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Studies into the electrochemical behaviour of pVFc films have shown how the voltammetric response is dependant on the anion present within the solution. 8,10,[21][22][23][24][25][26][27][28] The stability of the oxidation wave upon repetitive scanning was found to be dependant on the size of the anion, with larger anions producing less stable signals. This anion sensitivity was minimized by controlling both the scan rate and potential range.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of neutron reectivity data analysis 47 and the issues arising for samples involving "wet" interfaces under electrochemical control 48 have been described elsewhere. The variation with momentum transfer of reectivity from an interface, R(Q), is determined by the depth prole of the scattering length density, Nb, where N represents the concentration of scattering atoms present and b is their scattering length; the value of b is isotopically unique and medium independent.…”
Section: Discussionmentioning
confidence: 99%